The Unity of the Church: A Theological State of the Art and Beyond - Borght, Ed. A. J. G. van der (Studies in Reformed Theology, 2009)
This volume challenges the traditional low-key attitude towards the unity of the church within the Reformed tradition. It investigates theological aspects that contributed to a weak sensus unitatis and explores theological approaches that remedy this disease of division